PENINGKATAN KEMAMPUAN DASAR BAHASA INGGRIS ANAK MELALUI PEMBELAJARAN INTERAKTIF BERBASIS GAME, GERAK, DAN GAMBAR DI DESA DONGKO - Dinda Ayu Savitri; Aulia Amanda Samjar; Darwin Darwin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
This community service activity aims to improve the basic English skills of children in Dongko Village through an interactive learning method that combines elements of educational games, physical activity (movement), and image visualization. The identified problem was the children's low interest and understanding of English, which has been taught conventionally and less enjoyable. The implementation method was a participatory approach based on direct practice in study groups. The activity was carried out for three weeks with a series of programs ranging from introducing basic vocabulary (colors, animals, numbers), pronunciation practice, to reinforcement activities through educational games and song movements. The results of the community service showed a significant increase in vocabulary understanding, pronunciation, and active participation of children during the learning process. Children became more enthusiastic, confident, and able to apply vocabulary in simple contexts. Furthermore, the interactive approach encouraged the creation of a fun and inclusive learning atmosphere, thereby minimizing boredom and increasing learning effectiveness. Overall, this activity contributed to strengthening language literacy at the elementary level and was in line with the Freedom to Learn policy and Presidential Regulation Number 87 of 2017 concerning Strengthening Character Education. It is hoped that this learning model can be adopted by schools or other learning communities as an alternative strategy to improve the basic English skills of children in rural areas.